Organizational Prestige, Employee Engagement and Employee Retention in Selected Deposit Money Banks - Asinedu Kennedy Nwafili; Christopher Tuni Ijoyah; Joseph Chukwudi Okoh (PT Keberlanjutan Strategis Indonesia, 2026)
This study investigated the effect of organizational prestige and employee engagement on employee retention in selected deposit money banks in Delta State, Nigeria. A cross-sectional survey design was employed, collecting data from a sample of 370 bankers using a structured questionnaire. This study involved 10 deposit money banks with a population of 9,743, and using the Krejcie and Morgan table of sample size determination, a sample size of 370 respondents was drawn. Both descriptive and inferential statistical analytical tools were used in data analysis. Descriptive analysis was performed on the respondents' biographic data, while multiple regression and correlation analysis were carried out on the research hypotheses. Findings this study comes to the conclusion that employee engagement and organizational prestige improve staff retention at Deposit Money Banks in Delta State, Nigeria. The onus lies on the human resource department to ensure competent workers are recruited to guarantee organizational success or performance, create goodwill, be more socially responsible, provide efficient service delivery to reduce criticism, and comply with ethical regulations of the industry. Another factor that affects employee retention is employees' engagement. The human resources department should ensure employees are trained to improve their performance, commitment, loyalty and sense of ownership. More so, engaged employees should be recognized and rewarded intrinsically and extrinsically to enable them to feel fulfilled with the success of the organization.